Self-Compassion in Polytechnic Students: “Does Gender Count?” - Emma Dwi Ariyani ,Dini Hadiani (International Conference on Industrial Revolution for Polytechnic Education, 2020)
Self-compassion is the ability to entertain and care for oneself when suffering, failure and imperfection rather than self-criticism. This research was conducted with the aim to see the degree of self-compassion in polytechnic students and to find out whether there difference between the self-compassion of male and female students. By using Neff's Self-Compassion Scale (short form) measurement tool consisting of 12 items, the research method used was descriptive study with survey technique on 211 male students and 44 female students in the range age of 18 to 20. Results indicated that females (23% had high self-compassion) had slightly higher levels of self-compassion than males (22% had high self-compassion). Concerning the main components of self-compassion which are self-kindness, common humanity and mindfulness, there are differences in the dominant of component of self-compassion between male and female students. Female students have high self-kindness (64%) compared to component of mindfulness (57%) and common humanity (50%). Whereas male students have high common humanity (55%) compared to component of mindfulness (53%) and self-kindness (47%). These may inform the appropriate handing given to the students in terms of self-compassion.